2022
DOI: 10.12669/pjms.38.4.4635
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mentzer index for differentiating iron deficiency anemia and beta thalassemia trait in pregnant women

Abstract: Objective: To observe the role of Mentzer index for differentiating iron deficiency anemia (IDA) and beta thalassemia trait (β TT) in pregnant women. Methods: This cross-sectional study was conducted in Gynaecology & Obstetrics Department of Nishtar Medical University from October 2020 to March 2021. Non-consecutive sampling was applied. A total of 100 antenatal ladies with hemoglobin <11 gm/dl were included. Their complete blood counts were checked and Mentzer Index was calculated. Mentzer Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The study found that Mentzer index more than 13 (indicating IDA) and <13 (indicating thalassemia) was a reliable screening tool to differentiate between IDA and thalassemia. Similar findings were also reported by authors such as Tabassum et al [19] and Shah et al [20]…”
Section: Discussionsupporting
confidence: 92%
“…The study found that Mentzer index more than 13 (indicating IDA) and <13 (indicating thalassemia) was a reliable screening tool to differentiate between IDA and thalassemia. Similar findings were also reported by authors such as Tabassum et al [19] and Shah et al [20]…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, a study comparing RDW and Mentzer index found a sensitivity of 94.2% and 99.4% and PPV of 98.8% and 97.7% for the diagnosis of IDA when compared with serum ferritin among primigravids in Pakistan [ 21 ]. During iron deficiency, smaller RBCs are produced by the bone marrow resulting in a smaller RBC count and low MCV, thus a Mentzer index of >13 [ 58 ]. Therefore, RDW and Mentzer index can be used for early presumptive diagnosis of IDA and thus early initiation of treatment to avert the complications and long-term sequelae associated with IDA.…”
Section: Discussionmentioning
confidence: 99%
“…During iron de ciency, smaller RBCs are produced by the bone marrow resulting in a smaller RBC count and low MCV thus a Mentzer index of >13 (Tabassum et al, 2022). Therefore, RDW and Mentzer index can be used for early presumptive diagnosis of IDA and thus early initiation of treatment to avert the complications and long-term sequelae associated with IDA.…”
Section: Discussionmentioning
confidence: 99%